The Many Facets of Sphingolipids in the Specific Phases of Acute Inflammatory Response - Sabine Grösch; Alice V. Alessenko; Elisabetta Albi (Mediators of Inflammation)
This review provides an overview on components of the sphingolipid superfamily, on their localization and metabolism. Information about the sphingolipid biological activity in cell physiopathology is given. Recent studies highlight the role of sphingolipids in inflammatory process. We summarize the emerging data that support the different roles of the sphingolipid members in specific phases of inflammation: (1) migration of immune cells, (2) recognition of exogenous agents, and (3) activation/differentiation of immune cells.